Disrupsi antara Pemanfaatan Sungai dengan Ketidaksesuaiannya pada Regulasi, hingga Memunculkan Tindak Represif Pemerintah di Kelurahan Ditotrunan, Lumajang - Wisnu Aji; Yoga Septa Nurivandi; Muhamad Feri Herdiansyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Rivers are a part of nature that has many benefits for life, quite a few people want to be involved in its use. Even though they do not know the exact rules that cover them, the result is that at some point in their development they will be trapped by the applicable rules or laws. Like a tree that gets taller, it is at risk of being toppled by someone or even the wind. If this analogy is correlated to a group of residents in Ditotrunan Village who can make the best use of the river and are very popular, it must be based on the rules that must be followed. As a result, the form of use is demolition and removal efforts by the authorities. What's interesting is that it's not just the rules, but there are interests of each party as well as a sense of personal jealousy between one group and another. All of these things give rise to conflict between each group and also the local government.